Growth and photosynthetic performance of Fusarium solani infected Cucumis sativus L. treated with Trichoderma asperellum - Aris, Asma; Mohd Zainudin, Nur Ain Izzati; Ibrahim, Mohd Hafiz (Taylor and Francis Group, 2023)
Fusarium wilt disease caused by Fusarium species is a serious soilborne fungal disease that threatens the production of cucurbits in Malaysia. Despite multiple controls and measures, this economically important pathogenic genus continues to damage crops. Therefore, this study aims to compare the photosynthetic performance and to evaluate the gas exchange measurement of Fusarium solani-infected cucumber grown in the presence of Trichoderma asperellum, a biocontrol agent of Fusarium. Soil was infested with T. asperellum B1902 before planting cucumber seed inoculated or not inoculated with Fusarium. Thirty days post-inoculation (dpi), plant grown with T. asperellum B1902 had longer stems, more leaves and greater leaf area than that of the infected control. Furthermore, plants grown with T. asperellum B1902 had more efficient photosystem II (PSII) and enhanced photosynthetic performance. The data collected from this study contribute to our understanding of some of the mechanisms at play in the cucumber-Trichoderma–Fusarium interaction.